Three-dimensional scaffold with biological energy activity and preparation method thereof
A method for preparing a three-dimensional scaffold with bioenergetic activity addresses the issue of non-uniform pore structures by using tricarboxylic acid cycle intermediates and triols, resulting in a scaffold with uniform pores and improved tissue integration for bone repair.
Patent Information
- Application Number
- CN202411019404.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-13
AI Technical Summary
Existing three-dimensional scaffolds with bioenergetic activity have non-uniform and disconnected pore structures, which hinder tissue growth and nutrient exchange, limiting their effectiveness in bone defect repair.
A method involving prepolymerization of tricarboxylic acid cycle intermediates and triols, followed by 3D printing with a sacrificial template and isocyanate, and secondary cross-linking to create a scaffold with controlled pore size and connectivity, using specific weight ratios and conditions to ensure uniformity and stability.
The method produces a scaffold with uniform pore sizes and interconnected structures, enhancing tissue integration and energy supply to cells, promoting effective bone repair.
Smart Images

Figure CN119119412A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of biomaterials and tissue engineering technology, and in particular to a three-dimensional scaffold with bioenergetic activity and a preparation method thereof. Background Art
[0002] Large bone defects caused by severe trauma, infection, bone tumors, etc. need to be repaired by bone transplantation. In clinical practice, the transplantation materials for bone defects include autologous bone and allogeneic bone. Bone transplantation of autologous bone materials is the gold standard for bone defect treatment, but the amount of autologous bone materials is limited, and the bone harvesting stage is prone to matrix trauma and even infection, while allogeneic bone has the risk of immune rejection and disease transmission. However, the commonly used allogeneic bone biomaterials in the field of bone tissue engineering mainly include metal materials, bioceramics, polymer materials and composite materials. Among them, metal materials have good mechanical strength and biocompatibility, but lack biological activity and are difficult to degrade and absorb; bioceramics, such as hydroxyapatite, have excellent biocompatibility and osteoinduction properties, but have many disadvantages such as high brittleness, poor plasticity, and difficulty in processing; polymer materials generally include natural polymer materials and artificial synthetic polymer materials, and natural polymer materials are generally collagen, which has good biocompatibility and biodegradability, but the mechanical properties of collagen are insufficient; artificial synthetic polymer materials have good mechanical strength and processability, but generally lack biological activity; composite materials can use a variety of materials to achieve complementary advantages, which is a new hot spot in biomaterial research.
[0003] Bioenergetic active materials are a type of degradable regenerative medicine materials that are synthesized using tricarboxylic acid cycle metabolic intermediates such as succinic acid, fumaric acid or citric acid as starting molecules. These degradable regenerative medicine materials release small molecule fragments with energy active units through slow degradation. These small molecule fragments then enter cells and participate in the TCA cycle to significantly increase mitochondrial membrane potential, thereby promoting the generation of intracellular ATP to significantly accelerate bone repair. Therefore, degradable regenerative medicine materials will show important clinical transformation prospects.
[0004] At present, the preparation method of bioenergy active materials is the particle leaching-solvent volatilization method, that is, first dissolving the low molecular weight bioenergy material prepolymer in a polar solvent, then adding an isocyanate crosslinker, and placing it in a mold containing a porogen. After air drying and high temperature curing, it is soaked and washed in deionized water to remove the porogen to obtain a porous scaffold. However, the bioenergy material scaffold prepared by this method has the following disadvantages: the pore structure of the prepared bioenergy material scaffold model is single and cannot meet the needs of various complex clinical scenarios; the porous scaffold obtained by using a porogen has an uneven pore size, and the internal pores of the porous scaffold are not connected, which is not conducive to tissue growth and nutrient exchange between cells. Summary of the invention
[0005] The present application provides a three-dimensional scaffold with bioenergetic activity and a preparation method thereof to solve the following technical problem: how to improve the adjustability and uniformity of the pore structure of the three-dimensional scaffold with bioenergetic activity.
[0006] In a first aspect, the present application provides a method for preparing a three-dimensional scaffold having bioenergetic activity, the preparation method comprising:
[0007] The intermediate product of tricarboxylic acid cycle and triol are prepolymerized to obtain a prepolymer product with bioenergy activity;
[0008] Mixing a polar solvent and the prepolymer product having bioenergy activity to obtain a prepolymer solution;
[0009] Mixing the sacrificial template, isocyanate and the prepolymer solution to remove the polar solvent to obtain a printing slurry;
[0010] The printing slurry is 3D printed under preset printing conditions, so that the printing slurry is cross-linked and formed once to obtain a crude three-dimensional scaffold;
[0011] The crude three-dimensional scaffold is subjected to secondary cross-linking and then the cross-linked product is purified to obtain a three-dimensional scaffold with bioenergetic activity;
[0012] The weight m1 of the sacrificial template and the weight m2 of the prepolymer product in the prepolymer solution satisfy the relationship: m1:m2=2:1.
[0013] Optionally, the preset printing conditions include a preset printing spacing, a preset printing diameter and a preset printing temperature; the preset printing spacing is 0.8 mm to 1.2 mm, the preset printing diameter is 0.3 mm to 0.5 mm, and the preset printing temperature is 60° C. to 80° C.
[0014] Optionally, the weight m3 of the isocyanate and the weight m2 of the prepolymer product in the prepolymer solution satisfy the relationship: m3:m2≤1:5.
[0015] Optionally, the temperature of the secondary cross-linking molding is 150° C. to 155° C., the vacuum degree of the secondary cross-linking molding is ≤-100 kPa, and the reaction time of the secondary cross-linking molding is 12 h to 48 h.
[0016] Optionally, the temperature of the prepolymerization reaction is 150° C. to 155° C., the vacuum degree of the prepolymerization reaction is -85 kPa to 95 kPa, and the time of the prepolymerization reaction is ≥5 h.
[0017] Optionally, the amount n1 of the intermediate product of the tricarboxylic acid cycle and the amount n2 of the triol satisfy the relationship: n1:n2≥1:1.
[0018] Optionally, the intermediate product of the tricarboxylic acid cycle includes at least one of the following:
[0019] citric acid, alpha-ketoglutaric acid, succinic acid, fumaric acid, malic acid, and oxaloacetic acid;
[0020] The polar solvent includes acetone;
[0021] The triol includes glycerol;
[0022] The sacrificial template includes sodium chloride;
[0023] The isocyanate includes hexamethylene isocyanate.
[0024] Optionally, the weight m2 of the prepolymer product in the prepolymer solution and the weight m4 of the prepolymer solution satisfy the relationship: m2:m4≥0.1:1.
[0025] In a second aspect, the present application provides a three-dimensional scaffold with bioenergetic activity, wherein the three-dimensional scaffold is obtained by the preparation method described in the first aspect;
[0026] The pore size of the three-dimensional scaffold is 0.3 mm to 0.9 mm, and the porosity of the three-dimensional scaffold is ≥85%.
[0027] In a third aspect, the present application provides a bone defect transplant material, wherein the bone defect transplant material comprises the three-dimensional scaffold described in the second aspect.
[0028] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0029] The present application provides a method for preparing a three-dimensional scaffold with bioenergy activity, the preparation method comprising: prepolymerizing an intermediate product of a tricarboxylic acid cycle and a triol to obtain a prepolymer product with bioenergy activity; mixing a polar solvent and the prepolymer product with bioenergy activity to obtain a prepolymer solution; mixing a sacrificial template, an isocyanate and the prepolymer solution to remove the polar solvent to obtain a printing slurry; 3D printing the printing slurry under preset printing conditions to allow the printing slurries to undergo a primary cross-linking molding to obtain a crude three-dimensional scaffold; performing a secondary cross-linking molding on the crude three-dimensional scaffold, and then purifying the cross-linked product to obtain a three-dimensional scaffold with bioenergy activity; wherein the weight m1 of the sacrificial template and the weight m2 of the prepolymer product in the prepolymer solution satisfy the relationship: m1:m2=2:1. The preparation method first mixes the intermediate product of the tricarboxylic acid cycle and the triol to promote the initial polymerization reaction of the intermediate product of the tricarboxylic acid cycle and the triol, thereby obtaining a prepolymer product with bioenergy activity, and then mixes the prepolymer product with bioenergy activity and a polar solvent, so that the prepolymer product can be effectively dispersed in the polar solvent, thereby obtaining a prepolymer solution; then the sacrificial template, isocyanate and the prepolymer solution are mixed, and then through a one-time cross-linking molding method of 3D printing, the esterification reaction and cross-linking reaction between the isocyanate and the prepolymer solution can be used to increase the molecular weight of the prepolymer product while retaining a large number of hydrolyzable groups of the prepolymer molecular product, and in addition, the weight m1 of the sacrificial template and the weight m2 of the prepolymer product in the prepolymer solution can satisfy the relationship: m1:m2=2:1, and a sufficient amount of the sacrificial template can be introduced into the prepolymer solution. A sufficient amount of sacrificial template can, on the one hand, increase the amount of solute in the prepolymer solution to increase the viscosity of the prepolymer product, and on the other hand, can be removed from the prepolymer solution in the subsequent secondary cross-linking molding process to obtain fiber filaments with uniform pore size distribution and a crude three-dimensional scaffold composed of these fiber filaments with uniform pore size distribution, thereby realizing the regulation of the pore structure of the three-dimensional scaffold. Finally, the crude three-dimensional scaffold is subjected to a secondary cross-linking reaction to promote the further esterification reaction of the unreacted hydroxyl and carboxyl groups in the crude three-dimensional scaffold and form a cross-linked structure. These cross-linked structures can not only improve the stability of the pore structure between different fiber filaments in the three-dimensional scaffold, but also regulate the cross-linking density and the distribution of the pore structure of the three-dimensional scaffold, thereby realizing the controllable release of bioenergy active molecules, and then promoting the three-dimensional scaffold to meet the energy supply needs of cells in the repair process of different tissues. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0032] Figure 1 A schematic diagram of a process for preparing a three-dimensional scaffold with bioenergetic activity provided in an embodiment of the present application;
[0033] Figure 2 A product schematic diagram of a three-dimensional scaffold with bioenergetic activity provided in an embodiment of the present application;
[0034] Figure 3 A scanning electron microscope schematic diagram of a three-dimensional scaffold with bioenergetic activity provided in Example 1 of the present application;
[0035] Figure 4 A scanning electron microscope schematic diagram of a three-dimensional scaffold with bioenergetic activity after cells adhere to it provided in Example 1 of the present application;
[0036] Figure 5 This is a tissue morphology observation diagram of a three-dimensional scaffold with bioenergetic activity provided in Example 1 of the present application after being transplanted subcutaneously for 7 days;
[0037] Figure 6 This is a graph showing the degradation performance characteristics of the three-dimensional scaffold after being treated with different secondary cross-linking molding times provided in the embodiments of the present application;
[0038] Figure 7 A comparison diagram of the results of promoting ATP generation at the cellular level by a degradation product of a three-dimensional scaffold with bioenergetic activity and a commercial polymer PCL provided in Example 1 of the present application;
[0039] Figure 8 A graph showing the comparison of the results of an experiment on osteogenic differentiation of stem cells using a degradation product of a three-dimensional scaffold with bioenergetic activity and commercial high molecular weight polymer PCL provided in Example 1 of the present application, wherein the blue color is the ALP staining result of an early osteogenic differentiation indicator, and the red color is the Alizarin red staining result of calcium nodules formed by osteogenic differentiation;
[0040] Fig. 9 Schematic diagram of the three-dimensional stent product prepared in Example 1 and Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0042] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0043] In this document, the terms including "comprising" and the like mean "including but not limited to". "At least one" means one or more, "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in this application can be purchased on the market or prepared by existing methods.
[0044] Figure 1 The schematic diagram of the process of preparing a three-dimensional scaffold with bioenergetic activity provided in an embodiment of the present application is exemplarily shown;
[0045] like Figure 1 As shown, the present application embodiment provides a method for preparing a three-dimensional scaffold with bioenergetic activity, the preparation method comprising:
[0046] S1. prepolymerizing the intermediate product of the tricarboxylic acid cycle and the triol to obtain a prepolymer product having bioenergy activity;
[0047] S2. mixing a polar solvent and the prepolymer product having bioenergy activity to obtain a prepolymer solution;
[0048] S3. The sacrificial template, the isocyanate and the prepolymer solution are mixed to remove the polar solvent to obtain a printing slurry;
[0049] S4. 3D printing the printing slurry under preset printing conditions, so that the printing slurry is cross-linked once to obtain a crude three-dimensional scaffold;
[0050] S5. performing secondary cross-linking molding on the crude three-dimensional scaffold, and then purifying the cross-linked product to obtain a three-dimensional scaffold with bioenergetic activity;
[0051] The weight m1 of the sacrificial template and the weight m2 of the prepolymer product in the prepolymer solution satisfy the relationship: m1:m2=2:1.
[0052] It should be noted that after the secondary cross-linking molding, the crude three-dimensional scaffold needs to be washed to remove the sodium chloride in the crude three-dimensional scaffold to obtain a three-dimensional scaffold with bioenergy activity; deionized water can be used for the washing.
[0053] It should be noted that the sacrificial template needs to be ground by a ball mill and screened with a 74 μm mesh before use.
[0054] In some optional embodiments, the preset printing conditions include a preset printing spacing, a preset printing diameter and a preset printing temperature; the preset printing spacing is 0.8 mm to 1.2 mm, the preset printing diameter is 0.3 mm to 0.5 mm, and the preset printing temperature is 60° C. to 80° C.;
[0055] In these embodiments, the preset printing conditions may include a preset printing spacing, a preset printing diameter and a preset printing temperature. The spacing between adjacent fiber filaments in the crude three-dimensional scaffold can be controlled by controlling the printing spacing and printing diameter in the 3D printing stage to regulate the pore distribution of the three-dimensional scaffold, thereby improving the controllability of the pore structure of the three-dimensional scaffold; in addition, the preset printing temperature can be 60°C to 80°C, which can cause the printing slurry including the sacrificial template, isocyanate and prepolymer solution to be fully formed in the 3D printing stage, thereby obtaining a crude three-dimensional scaffold with a uniformly distributed pore structure.
[0056] The preset printing spacing may be 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm or 1.2 mm.
[0057] The preset printing diameter may be 0.30 mm, 0.35 mm, 0.40 mm, 0.45 mm or 0.50 mm.
[0058] The preset printing temperature may be 60°C, 65°C, 70°C, 75°C or 80°C.
[0059] In some optional embodiments, the weight m3 of the isocyanate and the weight m2 of the prepolymer product in the prepolymer solution satisfy the relationship: m3:m2≤1:5;
[0060] In these embodiments, the weight m3 of the isocyanate and the weight m2 of the prepolymer product in the prepolymer solution can satisfy the relationship: m3:m2≤1:5, which can ensure that there is a sufficient amount of isocyanate in the prepolymer solution. The sufficient amount of isocyanate can undergo esterification and cross-linking reactions with the prepolymer solution to increase the molecular weight of the prepolymer product while retaining a large number of hydrolyzable groups in the prepolymer molecular product.
[0061] In some optional embodiments, the temperature of the secondary cross-linking molding is 150° C. to 155° C., the vacuum degree of the secondary cross-linking molding is ≤-100 kPa, and the reaction time of the secondary cross-linking molding is 12 h to 48 h;
[0062] In these embodiments, the temperature of the secondary cross-linking molding can be 150°C to 155°C, and the vacuum degree of the secondary cross-linking molding is generally ≤-100kPa, and the reaction time of the secondary cross-linking molding can be 12h to 48h, which can promote the secondary cross-linking molding to be fully carried out, so as to promote the hydroxyl and carboxyl groups in the crude three-dimensional scaffold that have not fully reacted in the first cross-linking molding to continue to react to form a sufficient cross-linking structure, and the sufficient cross-linking structure can not only improve the stability of the pore structure between different fiber filaments in the three-dimensional scaffold, but also regulate the cross-linking density of the three-dimensional scaffold to improve the uniformity and controllability of the pore distribution of the three-dimensional scaffold.
[0063] The temperature of the secondary cross-linking molding can be 150°C, 151°C, 152°C, 153°C, 154°C or 155°C.
[0064] The reaction time of the secondary cross-linking molding can be 12h, 18h, 24h, 30h, 36h, 42h or 48h.
[0065] In some optional embodiments, the temperature of the prepolymerization reaction is 150° C. to 155° C., the vacuum degree of the prepolymerization reaction is -85 kPa to 95 kPa, and the time of the prepolymerization reaction is ≥ 5 h;
[0066] In these embodiments, the temperature of the prepolymerization reaction can be 150°C to 155°C, the vacuum degree of the prepolymerization reaction can be -85kPa to 95kPa, and the time of the prepolymerization reaction is generally ≥5h, which can promote the complete reaction between the intermediate product of the tricarboxylic acid cycle and the triol to obtain a sufficient amount of prepolymer product.
[0067] The temperature of the prepolymerization reaction may be 150°C, 151°C, 152°C, 153°C, 154°C or 155°C.
[0068] The vacuum degree of the prepolymerization reaction can be -85 kPa, -70 kPa, -55 kPa, -40 kPa, -25 kPa, -10 kPa, 5 kPa, 20 kPa, 35 kPa, 50 kPa, 65 kPa, 80 Pa or 95 kPa.
[0069] In an optional embodiment, the amount n1 of the intermediate product of the tricarboxylic acid cycle and the amount n2 of the triol satisfy the relationship: n1:n2≥1:1;
[0070] In these embodiments, the amount n1 of the intermediate product of the tricarboxylic acid cycle and the amount n2 of the triol may satisfy the relationship: n1:n2≥1:1,
[0071] In some optional embodiments, the intermediate product of the tricarboxylic acid cycle includes at least one of the following:
[0072] citric acid, alpha-ketoglutaric acid, succinic acid, fumaric acid, malic acid, and oxaloacetic acid;
[0073] The polar solvent includes acetone;
[0074] The triol includes glycerol;
[0075] The sacrificial template includes sodium chloride;
[0076] The isocyanate includes hexamethylene isocyanate;
[0077] In these embodiments, the intermediate product of the tricarboxylic acid cycle may include: at least one of citric acid, α-ketoglutaric acid, succinic acid, fumaric acid, malic acid and oxaloacetic acid, which can cover most of the bioenergetic active substances, thereby promoting the three-dimensional scaffold to have good bioenergetic active substances; in addition, the polar solvent may include acetone, which can promote the polar solvent to fully dissolve the prepolymer product to form a prepolymer solution; in addition, the triol may include glycerol, and the glycerol and the intermediate product of the tricarboxylic acid cycle can be fully prepolymerized to obtain a sufficient amount of prepolymer product; in addition, the sacrificial template may include sodium chloride, a On the one hand, the amount of solute in the prepolymer solution can be increased by sodium chloride to increase the viscosity of the prepolymer product. On the other hand, the sodium chloride can be separated from the three-dimensional scaffold by washing after the secondary cross-linking molding to obtain fiber filaments with uniform pore size distribution and a crude three-dimensional scaffold composed of these fiber filaments with uniform pore size distribution, thereby realizing the regulation of the pore structure of the three-dimensional scaffold; in addition, the isocyanate can include hexamethylene isocyanate, and the prepolymerization reaction can be fully carried out through the intermediate product of the hexamethylene isocyanate and carboxylic acid cycle to increase the molecular weight of the prepolymer product while retaining a large number of hydrolyzable groups of the prepolymer molecular product.
[0078] In some optional embodiments, the weight m2 of the prepolymer product in the prepolymer solution and the weight m4 of the prepolymer solution satisfy the relationship: m2:m4≥0.1:1.
[0079] In these embodiments, the weight m2 of the prepolymer product in the prepolymer solution and the weight m4 of the prepolymer solution can satisfy the relationship: m2:m4≥0.1:1, which can ensure that there is a sufficient amount of prepolymer product in the prepolymer solution, and the sufficient amount of prepolymer product can form a three-dimensional scaffold with sufficient mechanical properties and pore structure in the subsequent 3D printing stage.
[0080] Figure 2 A schematic diagram of a product of a three-dimensional scaffold with bioenergetic activity provided in an embodiment of the present application is exemplarily shown;
[0081] Based on a general inventive concept, such as Figure 2 As shown, the embodiment of the present application provides a three-dimensional scaffold with bioenergetic activity, and the three-dimensional scaffold is obtained by the preparation method;
[0082] The pore size of the three-dimensional scaffold is 0.3 mm to 0.9 mm, and the porosity of the three-dimensional scaffold is ≥85%.
[0083] The three-dimensional scaffold is obtained based on the above-mentioned preparation method. The specific steps of the preparation method can refer to the above-mentioned embodiment. Since the three-dimensional scaffold adopts part or all of the technical solutions of the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.
[0084] The pore size of the three-dimensional scaffold may be 0.3 mm to 0.9 mm, and the porosity of the three-dimensional scaffold is generally ≥ 85%, which indicates that the three-dimensional scaffold has a uniformly distributed pore structure.
[0085] The pore size of the three-dimensional scaffold can be 0.3 mm, 0.4 mm, 0.5 mm or 0.6 mm.
[0086] Based on a general inventive concept, an embodiment of the present application provides a bone defect transplant material, wherein the bone defect transplant material includes the three-dimensional scaffold.
[0087] The bone defect transplant material is realized based on the above-mentioned three-dimensional scaffold. The specific structure and composition of the three-dimensional scaffold can refer to the above-mentioned embodiment. Since the bone defect transplant material adopts part or all of the technical solutions of the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0088] It should be noted that
[0089] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards; if there are no corresponding industry standards, they are carried out according to common international standards, conventional conditions, or conditions recommended by the manufacturer.
[0090] Example 1
[0091] like Figure 1 As shown, a method for preparing a three-dimensional scaffold with bioenergetic activity comprises:
[0092] S1. Prepolymerizing 1 mol of the intermediate product of the tricarboxylic acid cycle and 1 mol of the triol to obtain a prepolymer product having bioenergy activity; specific steps:
[0093] The intermediate product of tricarboxylic acid cycle and triol are mixed in a three-necked flask and placed in an oil bath at 150° C. After the two are evenly mixed, the prepolymerization reaction conditions are controlled and stirred to obtain a colorless, transparent and flowing prepolymer product with bioenergy activity;
[0094] S2. mixing a polar solvent and a prepolymer product having bioenergy activity to obtain a prepolymer solution;
[0095] S3. The sacrificial template, isocyanate and prepolymer solution are placed in a fume hood and stirred to remove the polar solvent to obtain a printing slurry;
[0096] S4. Performing 3D printing on the printed slurry under preset printing conditions so that the printed slurry is cross-linked once to obtain a crude three-dimensional scaffold;
[0097] S5. performing secondary cross-linking molding on the crude three-dimensional scaffold to obtain a three-dimensional scaffold with bioenergetic activity;
[0098] The weight m1 of the sacrificial template and the weight m2 of the prepolymer product in the prepolymer solution satisfy the relationship: m1:m2=2:1.
[0099] The preset printing conditions include a preset printing spacing, a preset printing diameter and a preset printing temperature. The preset printing spacing is 0.9 mm, the preset printing diameter is 0.4 mm, and the preset printing temperature is 65°C.
[0100] The weight m1 of the sacrificial template and the weight m2 of the prepolymer solution satisfy the relationship: m1:m2=2:1; the weight m3 of the isocyanate and the weight m2 of the prepolymer solution satisfy the relationship: m3:m2=1:5.2.
[0101] The temperature of the secondary cross-linking molding is 150° C., the vacuum degree of the secondary cross-linking molding is -100 kPa, and the reaction time of the secondary cross-linking molding is 24 h.
[0102] The temperature of the prepolymerization reaction is 150° C., the vacuum degree of the prepolymerization reaction is -85 kPa, and the time of the prepolymerization reaction is 5 h.
[0103] The amount n1 of the intermediate product of the tricarboxylic acid cycle and the amount n2 of the triol satisfy the relationship: n1:n2=1:1.
[0104] The intermediate product of the tricarboxylic acid cycle is succinic acid;
[0105] The polar solvent is acetone;
[0106] The triol is glycerol;
[0107] The sacrificial template is sodium chloride;
[0108] The isocyanate is hexamethylene isocyanate.
[0109] The weight m4 of the prepolymer product and the weight m2 of the prepolymer solution satisfy the relationship: m4:m2=0.1:1.
[0110] Example 2
[0111] Based on the contents disclosed in Example 1, the following modifications are further made:
[0112] The default printing pitch is 0.8mm and the default printing diameter is 0.3mm.
[0113] The default printing temperature is 60°C.
[0114] The temperature of the secondary cross-linking molding is 155°C, and the reaction time of the secondary cross-linking molding is 48h.
[0115] The temperature of the prepolymerization reaction was 155° C., and the vacuum degree of the prepolymerization reaction was -85 kPa.
[0116] Example 3
[0117] Based on the contents disclosed in Example 1, the following modifications are further made:
[0118] The default print spacing is 1.2mm, and the default print diameter is 0.5mm.
[0119] The default printing temperature is 80°C.
[0120] The temperature of the secondary cross-linking molding is 153° C., and the reaction time of the secondary cross-linking molding is 12 h.
[0121] The temperature of the prepolymerization reaction was 153° C., and the vacuum degree of the prepolymerization reaction was 95 kPa.
[0122] Comparative Example 1
[0123] The scaffold was prepared using the particle leaching-solvent evaporation method. The specific process is as follows:
[0124] First, grind the salt particles to a suitable size, and then use a square hole sieve to sieve out particles of a suitable size range (generally 200μm to 300μm) according to the pore size requirements of the porous scaffold to obtain salt particles of uniform size.
[0125] The salt particles of uniform size are then tightly packed into a polypropylene mold, and then placed in a cell culture incubator at 95% humidity for 10 minutes. After the surface of the salt particles is slightly dissolved, they are taken out to obtain an interconnected salt particle template, thereby ensuring the connectivity of the prepared porous scaffold pores.
[0126] Next, according to the molecular weight of the prepolymer determined by gel permeation chromatography (GPC), an appropriate amount of hexamethylene diisocyanate (HDI) is added to the acetone solution of the prepolymer to form a mixed solution, and then the mixed solution is directly poured into the salt particle template obtained by the above method. After the acetone of the mixed solution is dissolved and volatilized at room temperature, the mixed solution and the salt particle template are placed in an oven at 80°C to continue the reaction for 48 hours. After the reaction is completed, a curing system is obtained.
[0127] The obtained solidification system is then immersed in deionized water for 3 days, and the water is changed every 12 hours to fully dissolve and remove the salt particle template. The obtained material is then freeze-dried to obtain a formed porous scaffold.
[0128] Comparative Example 2
[0129] Based on the contents disclosed in Example 1, the following modifications are further made:
[0130] The weight m1 of the sacrificial template and the weight m2 of the prepolymer product in the prepolymer solution satisfy the relationship: m1:m2=1:1.
[0131] Comparative Example 3
[0132] Based on the contents disclosed in Example 1, the following modifications are further made:
[0133] The weight m1 of the sacrificial template and the weight m2 of the prepolymer product in the prepolymer solution satisfy the relationship: m1:m2=3:1.
[0134] Comparative Example 4
[0135] Based on the contents disclosed in Example 1, the following modifications are further made:
[0136] The reaction time of the secondary cross-linking molding is 10h.
[0137] Comparative Example 5
[0138] Based on the contents disclosed in Example 1, the following modifications are further made:
[0139] The reaction time of secondary cross-linking molding is 72h.
[0140] Related experiments and effect data:
[0141] 1. Analysis of pore characteristics of the stent:
[0142] The pore structures of the stents obtained in the various embodiments and comparative examples were tested, and the results are shown in Table 1.
[0143] Table 1 Pore structure test results of the scaffolds obtained in various embodiments and comparative examples
[0144]
[0145] As shown in Table 1, the three-dimensional scaffolds of Examples 1 to 3 have good pore size distribution, while the scaffold obtained by the conventional particle leaching-solvent evaporation method in Comparative Example 1 has a relatively concentrated pore size distribution and a low degree of distribution uniformity. In addition, in the actual comparative experiment, it was found that Fig. 9As shown, insufficient sacrificial template is added in comparative example 2, which makes it difficult to form the three-dimensional scaffold, and the resulting product tends to be a liquid system, while excessive sacrificial template is added in comparative example 3, which makes it impossible to print the three-dimensional scaffold in the 3D printing stage.
[0146] However, the secondary cross-linking molding time in Comparative Example 4 was insufficient, and the three-dimensional scaffold melted and cracked in subsequent experiments. The secondary cross-linking molding time in Comparative Example 5 was too long, and the three-dimensional scaffold could not be degraded and generated degradation products in subsequent experiments.
[0147] 2. Surface feature detection of three-dimensional stents:
[0148] The three-dimensional scaffold (BAM) obtained in Example 1 was tested by scanning electron microscopy, and the results were as follows: Figure 3 As shown in the figure, this indicates that the three-dimensional scaffold has a multi-level pore structure and a high porosity. These multi-level pore structures include larger pore structures formed by multiple fiber filaments and smaller pore structures inside a single fiber filament. In addition, these multi-level pore structures are in a connected state, which makes these multi-level pore structures conducive to the implantation of a large number of cells, the growth of tissues, the transmission of oxygen and nutrients to tissues, and the excretion of metabolites of tissues or cells. The results are shown in Figure 4 Although the scaffold obtained in Comparative Example 1 has a certain porosity and pore size, the scaffold in Comparative Example 1 cannot adjust the porosity and pore size, and cannot ensure that the porous structure inside the scaffold is interconnected, which makes it have great limitations in the application of biological tissue engineering.
[0149] 3. Application experiment of three-dimensional scaffolds:
[0150] The three-dimensional scaffold obtained in Example 1 was implanted subcutaneously in Sprague-Dawley (SD) rats for 7 days, and the sections of the nearby tissues were observed. Figure 5 As shown, this indicates that the three-dimensional scaffold has no obvious immune rejection reaction, and the subcutaneous tissue grows into the three-dimensional scaffold to form a large number of blood vessels.
[0151] Specific steps: (1) A rat subcutaneous implantation model was used to evaluate the inflammatory response caused by the stent in vivo and the integration of the stent and tissue. The rats used were male SD rats weighing approximately 300 g.
[0152] (2) Before animal experiments, seal the three-dimensional scaffold with a sealing bag and use 60 Co Sterilize with radiation source. Then prepare chloral hydrate solution with a mass concentration of 4% using physiological saline.
[0153] (3) The rat was captured and weighed, and anesthetized with 4% chloral hydrate (10 mL / kg body weight) was injected intraperitoneally. An incision of about 1.5 cm in length was made on the back of the rat, and a three-dimensional scaffold (specification: 1 cm×1 cm×1 cm) was placed under the skin. The skin incision was sutured to complete the implantation of the three-dimensional scaffold.
[0154] (4) After 7 days of implantation of the three-dimensional scaffold, the rat was killed, the skin above the three-dimensional scaffold was cut open, and the three-dimensional scaffold and surrounding rat tissue were cut off and immersed in a 4% paraformaldehyde aqueous solution for fixation for 48 hours to obtain a tissue specimen.
[0155] (5) The tissue specimen is embedded in paraffin, sliced, and then stained with H&E. The stained sections can be observed under an optical microscope.
[0156] 4. Experiment on the effect of secondary cross-linking molding on three-dimensional scaffolds:
[0157] Using the contents disclosed in Example 1 and the conditions disclosed in Comparative Example 5, three-dimensional scaffolds with different secondary cross-linking treatments obtained at different secondary cross-linking molding times (12h, 24h, 48h and 72h) were investigated to investigate their effects on the degradation performance of the three-dimensional scaffolds:
[0158] The three-dimensional scaffolds prepared at different cross-linking times were weighed in a dry state (W0) and immersed in a PBS phosphate buffer solution (temperature of 37°C) to test their in vitro degradation ability. The samples were taken out at different time points (2 weeks, 4 weeks, 6 weeks, 8 weeks and 12 weeks), washed three times with deionized water, and then freeze-dried and weighed (W1). The ratio of the residual weight of the sample at each time point to the original weight was calculated, that is, W1 / W0×100%, and the value was plotted against time to obtain the degradation characteristic curve of the three-dimensional scaffold over time. The results are shown in FIG. Figure 6 shown.
[0159] Depend on Figure 6 It can be seen that the three-dimensional scaffold will form a cross-linked structure during the secondary cross-linking molding stage, and these cross-linked structures will also regulate the degradation performance of the three-dimensional scaffold.
[0160] 5. Experiment on 3D scaffolds stimulating cell ATP production:
[0161] The degradation solution of the three-dimensional scaffold in the above experiment at the 4th week was collected, freeze-dried, and dissolved again to prepare a 25× storage solution, which was sterilized by filtering with a 0.22μm sterile filter. Then, the degradation product stock solution of the PCL scaffold was prepared in the same way, and the two degradation product stock solutions (three-dimensional scaffold and PCL scaffold degradation product) were diluted with DMEM culture medium to obtain various test culture media (three-dimensional scaffold degradation product BAM-DP and PCL scaffold degradation product PCL-DP).
[0162] After the cells grow to 80% confluence, trypsin is used to digest the cells, and then a cell suspension of 1×104 cells / mL is prepared using complete culture medium and added to a 6-well plate for continued culture. After the cells adhere to the wall for 24 hours, the culture medium is discarded and replaced with different test culture medium (BAM-DP and PCL-DP). After the cells are treated for another 6 hours, the cells are lysed and the ATP content in the cell lysate is quantitatively detected using an ATP test kit. The specific experimental steps are as follows:
[0163] a) Sample preparation: remove the culture medium, add 200 μL of lysis buffer to the well plate to lyse the cells, and pipette repeatedly. After lysis, centrifuge at 4°C and 12000g for 5 minutes, and take the supernatant for subsequent determination. Then dilute the ATP standard solution with ATP detection lysis buffer to several concentrations such as 0.01μmol / L, 0.03μmol / L, 0.1μmol / L, 0.3μmol / L, 1μmol / L, 3μmol / L and 10μmol / L for making the standard curve for ATP detection.
[0164] b) Prepare ATP detection working solution: dilute ATP detection reagent with ATP detection reagent diluent at a volume ratio of 1:9 to obtain ATP detection working solution. Store on ice for later use.
[0165] c) Determination of ATP concentration: Take 100 μL of ATP detection working solution into the detection well or detection tube. Leave it at room temperature for 3-5 minutes to consume the background ATP. Add 20 μL of sample or standard to the detection well, quickly mix it with a gun, and measure the RLU value with an enzyme marker after 2 seconds. Then calculate the ATP concentration in the sample based on the standard curve. Record the ATP concentration values of each 3D scaffold degradation product BAM-DP and PCL scaffold degradation product PCL-DP. The results are as follows: Figure 7 shown.
[0166] Depend on Figure 7 It can be seen that compared with the degradation product of commercial high molecular polymer (PCL-DP), the succinic acid in the degradation product of the three-dimensional scaffold (BAM-DP) can be effectively absorbed by cells or tissues to promote the generation of ATP in cells or tissues.
[0167] 7. Experiment on the effect of three-dimensional scaffold on osteogenic differentiation of stem cells:
[0168] In order to study the effect of the degradation products of the three-dimensional scaffold provided in the examples of the present application on the in vitro differentiation of stem cells, differentiation medium containing the degradation product of the three-dimensional scaffold (BAM-DP) and the degradation product of the commercial polymer PCL were used.
[0169] (PCL-DP) differentiation medium.
[0170] When the cells grew to 80% confluence, trypsin was used to digest the cells and then complete culture medium was used to prepare 1×10 4 The cell suspension was then added to a 6-well plate for further culture.
[0171] After the cells adhered for 24 hours, the culture medium was discarded and replaced with osteogenic differentiation medium containing BAM-DP or PCL-DP. The cells were treated for 7 days and then stained with ALP alkaline phosphatase dye. After 14 days of culture, Alizarin red staining (ARS) was used to evaluate the level of calcium nodule formation in the cells. Figure 8 shown.
[0172] Depend on Figure 8 It can be seen that the degradation products of the three-dimensional scaffold can significantly promote the osteogenic differentiation of stem cells. Therefore, transplanting the three-dimensional scaffold as a bone transplant material into the bone defect site can effectively accelerate the osteogenic differentiation of cells.
[0173] In summary, the embodiment of the present application provides a method for preparing a three-dimensional scaffold with bioenergy activity. The method first mixes a sacrificial template, isocyanate and a prepolymer solution with bioenergy activity energy, and then performs 3D printing to allow the sacrificial template, isocyanate and prepolymer solution to undergo a primary cross-linking molding, and then undergoes a secondary cross-linking molding and purification. The sacrificial template in the three-dimensional scaffold can be removed during the purification stage to regulate the pore structure of the three-dimensional scaffold; in addition, the degradation degree of the three-dimensional scaffold can be regulated by the secondary cross-linking molding method, thereby achieving the controlled release of bioenergy active molecules in the three-dimensional scaffold, and further enabling the three-dimensional scaffold to meet the energy supply needs of cells during the repair of different tissues.
[0174] In addition, compared with the prior art, the prepolymers of bioenergy active materials have a low molecular weight and are in a flowing state as a whole, and cannot be directly 3D printed to customize personalized scaffolds. Therefore, the three-dimensional scaffold can only be prepared through a single determined model. The present application provides a method for preparing a three-dimensional scaffold with bioenergy activity, which performs 3D printing on bioenergy active materials for the first time, and can customize three-dimensional scaffolds with different pore structure distributions and different porosities to meet the needs of different tissue engineering projects.
[0175] In addition, an embodiment of the present application provides a three-dimensional scaffold with bioenergetic activity, which has a suitable pore size, a high porosity and a connected pore morphology, which is conducive to the implantation of a large number of cells, the growth of tissues, the transmission of oxygen and nutrients to tissues, and the excretion of metabolites of tissues or cells and other physiological activities.
[0176] In addition, a bone defect transplant material provided in an embodiment of the present application can be perfectly adapted to the bone defect site according to the shape and size requirements of the patient's defect site using 3D printing technology combined with secondary cross-linking molding technology, which helps to reduce bone loss and shorten operation time, and is of great significance in orthopedic clinical treatment.
[0177] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.
Claims
1. A method for preparing a three-dimensional scaffold with bioenergetic activity, characterized in that: The preparation method comprises: The intermediate product of tricarboxylic acid cycle and triol are prepolymerized to obtain a prepolymer product with bioenergy activity; Mixing a polar solvent and the prepolymer product having bioenergy activity to obtain a prepolymer solution; Mixing the sacrificial template, isocyanate and the prepolymer solution to remove the polar solvent to obtain a printing slurry; The printing slurry is 3D printed under preset printing conditions, so that the printing slurry is cross-linked and formed once to obtain a crude three-dimensional scaffold; The crude three-dimensional scaffold is subjected to secondary cross-linking and then the cross-linked product is purified to obtain a three-dimensional scaffold with bioenergetic activity; The weight m1 of the sacrificial template and the weight m2 of the prepolymer product in the prepolymer solution satisfy the relationship: m1:m2=2:
1.
2. The preparation method according to claim 1, characterized in that: The preset printing conditions include a preset printing spacing, a preset printing diameter and a preset printing temperature; the preset printing spacing is 0.8 mm to 1.2 mm, the preset printing diameter is 0.3 mm to 0.5 mm, and the preset printing temperature is 60° C. to 80° C.
3. The preparation method according to claim 1, characterized in that: The weight m3 of the isocyanate and the weight m2 of the prepolymer product in the prepolymer solution satisfy the relationship: m3:m2≤1:
5.
4. The preparation method according to claim 1, characterized in that: The temperature of the secondary cross-linking molding is 150° C. to 155° C., the vacuum degree of the secondary cross-linking molding is ≤-100 kPa, and the reaction time of the secondary cross-linking molding is 12 h to 48 h.
5. The preparation method according to claim 1, characterized in that: The temperature of the prepolymerization reaction is 150° C. to 155° C., the vacuum degree of the prepolymerization reaction is -85 kPa to 95 kPa, and the time of the prepolymerization reaction is ≥5 h.
6. The preparation method according to claim 1, characterized in that: The amount n1 of the intermediate product of the tricarboxylic acid cycle and the amount n2 of the triol satisfy the relationship: n1:n2≥1:
1.
7. The preparation method according to claim 1, characterized in that: The intermediate products of the tricarboxylic acid cycle include at least one of the following: citric acid, alpha-ketoglutaric acid, succinic acid, fumaric acid, malic acid, and oxaloacetic acid; The polar solvent includes acetone; The triol includes glycerol; The sacrificial template includes sodium chloride; The isocyanate includes hexamethylene isocyanate.
8. The preparation method according to claim 1, characterized in that: The weight m2 of the prepolymer product in the prepolymer solution and the weight m4 of the prepolymer solution satisfy the relationship: m2:m4≥0.1:
1.
9. A three-dimensional scaffold with bioenergetic activity, characterized in that: The three-dimensional scaffold is obtained by the preparation method according to any one of claims 1 to 8; The pore size of the three-dimensional scaffold is 0.3 mm to 0.9 mm, and the porosity of the three-dimensional scaffold is ≥85%.
10. A bone defect transplant material, characterized in that: The bone defect transplant material comprises the three-dimensional scaffold as claimed in claim 9.
Citation Information
Cited By
Osteochondral scaffold with biological energy activity and preparation method of osteochondral scaffold
CN119656377A
